2001
DOI: 10.1002/ccd.1192
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ulnar artery approach for coronary angiography: A preliminary report in nine patients

Abstract: The radial artery approach is becoming more popular for diagnostic cardiac catheterization and interventional procedures because of its lower incidence of access site complications and decreased patient discomfort after the procedure. However, Allen's test reveals inadequate blood supply through the ulnar artery to the hand, and therefore the approach does not seem to be suitable in 10%-30% of patients. Here we demonstrated a new percutaneous ulnar artery approach for coronary angiography in nine patients. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 9 publications
2
33
0
4
Order By: Relevance
“…The theoretical concern for permanent nerve trauma arises from the ulnar artery-to-nerve anatomic proximity and the difficult arterial access in many patients. This study substantially extended the limited information on this topic [4][5][6][7][8][9][10][11] and suggests that ulnar nerve palsy is unlikely after transulnar cannulation.…”
Section: The Ulnar Arterysupporting
confidence: 52%
See 1 more Smart Citation
“…The theoretical concern for permanent nerve trauma arises from the ulnar artery-to-nerve anatomic proximity and the difficult arterial access in many patients. This study substantially extended the limited information on this topic [4][5][6][7][8][9][10][11] and suggests that ulnar nerve palsy is unlikely after transulnar cannulation.…”
Section: The Ulnar Arterysupporting
confidence: 52%
“…In turn, this anatomic advantage of the radial artery has been associated with less local hemorrhagic complications and possibly more favorable long-term outcome. [1][2][3] The ulnar artery is rarely selected for coronary procedures in the context of a primary angiographic strategy, [4][5][6][7][8][9][10][11] despite the following potential advantages of the transulnar access:…”
mentioning
confidence: 99%
“…Case series with varying number of patients [6][7][8][9] followed up with ultrasound examinations, the largest of which involved 172 patients [10] have shown that the Trans ulnar approach is an additional option when the radial artery access is not available. This technique is associated with low incidence of major vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…The ulnar artery mean diameter was 2.7 6 ± 0.42 mm that could be larger or smaller than the radial artery branching from the same branchial artery or even reported to be similar in size. 4,5,[11][12][13] Via a TU approach, 4 and 5 French sheaths and catheters were used for diagnostic purposes in most of the cases. 6F sheaths were needed in 46%, when demanding techniques such as the kissing balloon technique, intravascular ultrasound, and rotational atherectomy, with high success and low complication rates.…”
Section: )mentioning
confidence: 99%